Civil society and development: a reconceptualisation. Issue 1 (2nd January 2017) - Dagher, Ruby
ABSTRACT: Civil society is promoted as an integral player for democratic development, the establishment of good governance, and the promotion of human rights. This article assesses this normative belief by examining conceptually the societal space thereby defined. The analysis draws on the presence of both civil and "uncivil" groups; the impact of time on the objectives and actions of both groups; the groups' straddling strategies between civil and "uncivil" spaces; and the difference between the locals' definition of civil society and that of international donors. Building on empirical case studies, the article proposes a reconceptualisation of the societal space.